2012
DOI: 10.1002/jobm.201100456
|View full text |Cite
|
Sign up to set email alerts
|

CcpA and three newly identified proteins are involved in biofilm development in Lactobacillus plantarum

Abstract: The aim of this study was to identify genes involved in biofilm development in the probiotic lactic acid bacterium Lactobacillus plantarum. The ability of L. plantarum LM3 and of some derivative mutant strains to form biofilm has been investigated. Biofilm microtitre plate assays showed that L. plantarum LM3-2, carrying a null mutation in the ccpA gene, coding the CcpA master regulator, was partially impaired in biofilm production compared to wild type (LM3). Moreover, we found three genes in the L. plantarum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The participation of eDNA as part of the biofilm matrix was previously shown for other species including Listeria monocytogenes (Harmsen et al, 2010), Streptococcus pneumoniae (Hall- Stoodley et al, 2008), Staphylococcus aureus (Mann et al, 2009) and for L. plantarum LM3 (Muscariello et al, 2013), however, culturable cells in the biofilm were not quantified and neither an assessment of the correlation, if any, between CV staining and CFUs.…”
Section: Discussionmentioning
confidence: 96%
“…The participation of eDNA as part of the biofilm matrix was previously shown for other species including Listeria monocytogenes (Harmsen et al, 2010), Streptococcus pneumoniae (Hall- Stoodley et al, 2008), Staphylococcus aureus (Mann et al, 2009) and for L. plantarum LM3 (Muscariello et al, 2013), however, culturable cells in the biofilm were not quantified and neither an assessment of the correlation, if any, between CV staining and CFUs.…”
Section: Discussionmentioning
confidence: 96%
“…The regulatory role of CcpA in biofilm formation has also been recently reported for Lactobacillus plantarum and Streptococcus gordonii . In Lactobacillus plantarum , CcpA transcriptionally regulates the expression of flmA , flmB , and flmC genes, which code for homologues of the Streptococcus mutans BrpA (biofilm regulatory protein A) . The ccpA mutant strain of Streptococcus gordonii is severely impaired in biofilm forming ability with a defect in extracellular polysaccharide production .…”
Section: Carbon and Nitrogen Sourcementioning
confidence: 99%
“…The mechanism of adhesion of lactobacilli to the intestinal tract of animals or humans is complicated and poorly clarified. Slps of lactobacilli were confirmed as adhesins that play an important role in adherence to the epithelial cells (Johnson-Henry et al 2007;Muscariello et al 2013). Our previous results showed that the putative Slps from lactobacilli are involved in adhesion of lactobacilli and inhibition of pathogens to adhere to Caco-2 cell lines (Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 82%